2011
DOI: 10.3758/s13428-011-0085-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of the RoboFlag synthetic task environment to investigate workload and stress responses in UAV operation

Abstract: Use of unmanned aerial vehicles (UAVs) is an increasingly important element of military missions. However, controlling UAVs may impose high stress and workload on the operator. This study evaluated the use of the RoboFlag simulated environment as a means for profiling multiple dimensions of stress and workload response to a task requiring control of multiple vehicles (robots). It tested the effects of two workload manipulations, environmental uncertainty (i.e., UAV's visual view area) and maneuverability, in 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
12
1
4
Order By: Relevance
“…Excessive trust may be stress-reducing in the short-term, but liable to elicit stress response after a time delay, as the consequences of undetected machine failures become apparent (an example of the T 2 SO perspective). Similarly, interface features such as displays that are hard to interpret, unresponsive controls, and lack of critical information are domain-specific stressors (e.g., Guznov, Matthews, Funke, & Dukes, 2011).…”
Section: Resilience In Unmanned Vehicle Operationmentioning
confidence: 99%
“…Excessive trust may be stress-reducing in the short-term, but liable to elicit stress response after a time delay, as the consequences of undetected machine failures become apparent (an example of the T 2 SO perspective). Similarly, interface features such as displays that are hard to interpret, unresponsive controls, and lack of critical information are domain-specific stressors (e.g., Guznov, Matthews, Funke, & Dukes, 2011).…”
Section: Resilience In Unmanned Vehicle Operationmentioning
confidence: 99%
“…Within specific task environments, we can also examine moderator effects of task parameters. For example, the stress profile is influenced by manipulations of uncertainty and robot maneuverability (Guznov, Matthews, Funke, & Dukes, 2011) and by positive versus negative feedback messages referring to the quality of operator performance (Kustubayeva et al, 2012). As a further example, Szalma and Teo (2012) showed that increasing the number of displays to be monitored systematically increased distress and reduced worry.…”
Section: Profiling the Impact Of Task Characteristicsmentioning
confidence: 99%
“…Auch wenn die Fernsteuerung solcher Maschinen die Gewähr für das physische Wohlbefinden des Operateurs darstellt, sind diese einem enorm hohen mentalen Druck unterlegen [13,26]. Es gehört zu ihren Aufgaben, Flugbahnen zu kontrollieren, Risiken einzuschätzen und Waffen gezielt einzusetzen [26].…”
Section: Psychische Belastungenunclassified
“…Auch wenn die Fernsteuerung solcher Maschinen die Gewähr für das physische Wohlbefinden des Operateurs darstellt, sind diese einem enorm hohen mentalen Druck unterlegen [13,26]. Es gehört zu ihren Aufgaben, Flugbahnen zu kontrollieren, Risiken einzuschätzen und Waffen gezielt einzusetzen [26]. So gehört es für Piloten der United States Air Force (USAF) zu ihrem gewohnten Alltag, feindliche Objekte über eine bestimmte Zeit hinweg zu verfolgen, anzuvisieren und schlussendlich zu zerstören [13].…”
Section: Psychische Belastungenunclassified